Pemetaan Tren Penelitian Literasi Artificial Intelligence 2019 - 2025 : Analisis Bibliometrik - Shiefti Dyah Alyusi; Siti Muzaroh; Sukma Kartikasari (Perpustakaan Universitas Gadjah Mada, 2026)
The development of AI literacy as a key competency in the 21st century should be accompanied by a comprehensive knowledge map of the direction, structure, and dynamics of global research. The mapping is important to ensure that curriculum development, education policies, and research agendas run systematically and evidence-based. However, factual conditions suggest that most AI literacy research still focuses on the formulation of definitions, conceptual frameworks, and implementation in a limited scope. The study aims to map AI literacy research trends using a bibliometric approach based on data from Scopus, which is analyzed with the help of VOSviewer software. A total of 289 publications published between 2019 - 2025 were analyzed based on publication distribution, dominant keywords, collaboration networks between authors, and relationships between articles through bibliographic coupling. The results show an increasing trend in the number of publications over the past five years, with significant spikes in 2024 and 2025. These findings provide an overview of further research opportunities related to AI literacy. In addition, the study recommends the need for education policies that support the systematic integration of AI literacy into formal education curricula, especially in developing countries. With a bibliometric approach, this study is expected to be a strategic reference for researchers, educators, and policymakers in designing relevant, inclusive, and sustainable artificial intelligence literacy programs in the era of digital transformation.